»On krasi mesto – mesto naj podpira njega!« - Ferlež, Jerneja (Zgodovina za vse, 2025)
Photographer Josip Pelikan spent most of his career in Celje, where his legacy is well researched and documented and represents an important part of the city's heritage, but this text looks back to his less well-known quarter-century formative period in Idrija between 1894 and 1919. Through registers and other sources, it sheds light on the photog-rapher's childhood and youth, as well as on the life of his ancestors, especially his mother in her birthplace Rožmítal pod Třemšínem in the Czech Republic. It describes the arrival of young Pelikan from Trbiž, where he was born, to Idrija, where he spent a quarter of a century, and the circumstances of his upbringing and development into a renowned professional photographer. It also focuses on the buildings in which he lived and worked, and the people he grew up with. The paper highlights the surviving pho-tographs of Josip Pelikan, Anton Schmeiler and Barbara Kastner from Trbiž, Idrija and Brežice, and raises the ques-tion of the influence of buildings on personal and collective memory, or on the processes of heritage in general.
Keywords: collective memory; fotografski ateljeji; Gospodarski kriminal; Idrija; Josip Pelikan; kolektivni spomin; Pelikan, Josip; photographic studios; poklicni fotografi; professional photographers